Pengaruh Media Pembelajaran Phet Simulation Terhadap Hasil Belajar Kelas X Pada Materi Geometri Molekul - Fitri Pratiwi; Haratua Tiur Maria Silitonga; Venny Karolina (Departement of Mathematics Education, 2023)
This research aims to determine the influence of PhET simulation media and student learning outcomes on molecular geometry material. The method used in this research is the experimental method. The form of experiment used in this research was One Group pretest-posttest and a class X sample of 20 people. Data analyzed using pretest and posttest are presented in bar charts and data management uses SPSS. The average results of the pretest and posttest scores were quite different, 41.5 and 67. Based on the results of data management using the Wilcoxon test, a value of 0.00 was obtained, less than 0.05 and the n-gain test criteria was 0.433, the medium category was obtained. Based on the research results, there is an influence of the use of PhET Simulation learning media on the learning outcomes of class X students in molecular geometry chemistry material